Cenozoic Uplift and Volcanism of Hangai Dome, Central Mongolia Triggered by Lower Mantle Upwellings. Issue 8 (25th April 2023) - Wu, Yingkai; Bao, Xuewei
Abstract: The mechanisms of surface uplift of Hangai Dome (>2 km) and formation of Cenozoic intraplate volcanism in central Mongolia remain vigorously debated. Here we directly investigate the mantle transition zone (MTZ) structure beneath central Mongolia to explore whether the deep mantle geodynamical processes have played a role. Our results reveal significant MTZ thinning of 8–13 km in three subareas mainly caused by the uplifted 660‐km discontinuity (∼10 km). In addition, the 410‐km discontinuity is depressed beneath the Hangai Dome (∼6 km) and the northern portion of the study area (10–15 km). These observations provide direct evidences for intracontinental mantle upwellings from the lower to the upper mantle, causing the Cenozoic uplift and basaltic volcanism of central Mongolia. Furthermore, these mantle upwellings are relatively sluggish compared to canonical mantle plumes based on the small magnitude of MTZ thinning and thus relatively moderate thermal anomaly within the MTZ (62–100 K). Plain Language Summary: The mechanisms of Cenozoic uplift and volcanism of Hangai Dome, central Mongolia have puzzled geoscientists for decades. The existence and role of the mantle upwelling that rises from the lower mantle remain highly debated. Here we investigate the mantle transition zone (MTZ) delimited by 410‐km (d410) and 660‐km (d660) discontinuities, which could provide direct constrains for thermal structure within the MTZ. Our results reveal slightly depressed d410 beneath Hangai Dome (∼6 km) and prominently uplifted d660 (∼10 km) and thinned MTZ (8–13 km) in three subareas, providing direct evidences for mantle upwellings rising from the lower mantle, traversing the MTZ, ascending to the upper mantle, and significantly contributing to the surface uplift and formation of Cenozoic intraplate volcanism. Specially, the lower mantle upwellings are cooler and more sluggish than mantle plumes due to the mild thermal anomaly within the MTZ (62–100 K) estimated from the relatively small magnitude of MTZ thinning. Key Points: Detailed structure of the mantle transition zone (MTZ) beneath central Mongolia suggests the existence of lower mantle upwellings The MTZ thickness is prominently thinned by 8–13 km in three subareas mainly due to the uplifted 660‐km discontinuity (∼10 km) The lower mantle upwellings are more sluggish than canonical mantle plumes due to the moderate thermal anomaly (62–100 K) within the MTZ